Application of Hydro-Geochemical and Geo-Electrical Techniques to Identify the Impact of Tsunami in the Coastal Groundwater - S., Chidambaram; A.L., Ramanathan; M.V., Prasanna; R., Manivannan (IntechOpen, 2011)
None